Strategic communication : campaign planning - Mahoney, James Scott, 1947- (United Nation, 2023)
"Strategic Communication deals with the principles behind strategic communication planning. It covers the professional practice steps involved in researching, planning, writing, evaluating and implementing a communication strategy. This book links strategic communication campaign planning to medium and long-term business activity and to how organisations deal with issues. This thoroughly revised third edition includes: New international cases and professional exercises that will enable students to work through the cases and apply theory to real-life situations; New discussion questions on important aspects of campaign planning; Chapter exercises that encourage students to think more broadly about communication strategy and work through the particular aspects of a strategy; In Theory panels that highlight key theories and demonstrate important links between theory and practice Accessible and comprehensive, this is an essential text for students of professional communication and professionals transitioning into the field of Strategic Communication"--